MATHEMATICAL CRITICAL THINKING ABILITY AND DISPOSITION (Experiment with Vocational High School Students Using Scientific Approach) - Utari Sumarmo; Agus Kusnadi; Rippi Maya (Kopertis Region IV Jabar and Banten, 2018)
This study is a pretest-postest experiment control group design having a goal to analyze the role of scientific approach on mathematical critical thinking ability and disposition. The study involved 70 eleventh grade of vocational high school students, a test on mathematical critical thinking, a disposition scale, and a scale of students’ perception on scientific approach. The study revealed that students getting treatment on scientific approach attained better grades on mathematical critical thinking ability and disposition than that of students taught by expository teaching, though the mathematical critical thinking ability grades were at medium level and the grades of disposition were at fairly good level. Besides that, students performed positive opinions toward scientific approach and there was association between mathematical critical thinking ability and disposition.